Experience of the successful treatment with canakinumab of a patient with NLPC4-associated autoinflammatory syndrome with enterocolitis - T. V. Sleptsova; E. I. Alexeeva; K. V. Savost’yanov; A. A. Pushkov; T. M. Bzarova; S. I. Valieva; O. L. Lomakina; R. V. Denisova; K. B. Isaeva; E. G. Chistyakova (Педиатрическая фармакология)
The article shows the observation of rare NLPC4-associated autoinflammatory syndrome with enterocolitis and familial cold urticaria. Diagnosis is confirmed molecularly-genetically: previously not described mutation c.928C>T in the heterozygous state in NLRC4 gene is discovered by a method of the new generation sequencing. The use of a monoclonal antibody to the interleukin 1 canakinumab provided complete relief of fever and skin and intestinal symptoms in just 1 week of treatment. Later the signs of inflammation have disappeared completely; the patient’s quality of life improved and life-threatening complications were prevented. The above example demonstrates the high clinical efficacy of canakinumab in the patient with NLRC4-associated autoinflammatory syndrome and suggests promising therapeutic use of interleukin 1 blockers in such patients. There were no adverse events during canakinumab therapy.